2021
DOI: 10.1021/acsinfecdis.1c00076
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing Infectious Disease Hits as Anti-Cryptosporidium Leads

Abstract: New drugs are critically needed to treat Cryptosporidium infections, particularly for malnourished children under 2 years old in the developing world and persons with immunodeficiencies. Bioactive compounds from the Tres-Cantos GSK library that have activity against other pathogens were screened for possible repurposing against Cryptosporidium parvum growth. Nineteen compounds grouped into nine structural clusters were identified using an iterative process to remove excessively toxic compounds and screen relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Our previous experience comparing target-based screens to cell-based assays suggests that IC 50 less than 2 μM is necessary to see growth inhibition, thus it is not surprising that the low affinity inhibitors did not show inhibition in this assay. 39 Crystallizable Constructs of CpNMT Provide A Platform for Structure-Guided Inhibitor Development. We performed a screening of CpNMT constructs to identify ones that could be overexpressed and used to generate highresolution co-crystal structures of the enzyme bound to the inhibitors (Supplementary Methods and Tables S1 and S2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous experience comparing target-based screens to cell-based assays suggests that IC 50 less than 2 μM is necessary to see growth inhibition, thus it is not surprising that the low affinity inhibitors did not show inhibition in this assay. 39 Crystallizable Constructs of CpNMT Provide A Platform for Structure-Guided Inhibitor Development. We performed a screening of CpNMT constructs to identify ones that could be overexpressed and used to generate highresolution co-crystal structures of the enzyme bound to the inhibitors (Supplementary Methods and Tables S1 and S2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…We found that compound 1 , but not 2 or 9 , inhibits growth of parasite on HCT-8 cells (Figure ). Our previous experience comparing target-based screens to cell-based assays suggests that IC 50 less than 2 μM is necessary to see growth inhibition, thus it is not surprising that the low affinity inhibitors did not show inhibition in this assay …”
Section: Resultsmentioning
confidence: 99%
“…Phenotypic screens may identify compounds with novel targets or pathways, with the caveat that target identification and MoA studies are often needed after active compounds are discovered. There have been a number of additional phenotypic screens for Cryptosporidium drug discovery [ 25 , 26 ], though the compounds discussed in this review are the most advanced.…”
Section: Pipeline Of Emerging Cryptosporidiosis Therapeuticsmentioning
confidence: 99%
“…Drug repurposing involves the identification of new uses of approved drugs, while target repurposing, for infectious diseases, involves the matching of pathogen targets with their human orthologs in which hits/leads have been described ( 29 , 30 ). Among infectious diseases, other pragmatic approaches to accelerate new drug-discovery efforts include the repurposing of bioactive compounds with activity in similar pathogens ( 26 ). High-throughput screening of kinase libraries such as the publicly available GlaxoSmithKline (GSK) Published Kinase Inhibitor Set (PKIS) and other kinase collections have resulted in identification of hit compounds against other parasites such as Plasmodium falciparum and Trypanosoma brucei and thus provided an excellent starting point for further optimization and validation of compounds using target-based approaches ( 29 , 31 33 ).…”
Section: Introductionmentioning
confidence: 99%